(untitled) (London Journal of Research In Science: Natural and Formal, 2024)
Paramos are an important mountain ecosystem; they are essential water supplier to Andean population. Understanding its hydrological function is fundamental to preserve it, manage and to implement conservation programs. Little is known about the effect of paramos’ vegetation upon the water fluxes. Evapotranspiration (EVT) is the main water output in this ecosystem and the most complex to measure. Using an ecosystem approach was estimated EVT through the net daily variation of soil water content (SWC) and was abstracted information about the other fluxes. The aim was assessing the effect of different plant life forms upon SWC and ETV. Therefore, TDR sensors were installed in the first 10cm into soils beneath different sort of covers (rossette, shrub and bare soil) and they were set up 10minute register, from March 2012 to November 2013. The shrub kept a SWC mean 36% higher than the rosette and like bare soils (bs). In the dry season, the rosette hold a SWC close to bs, but its SWCs were more stable, despite the rain decrease and its fluctuation. In bs the soil water discharge was two times faster than under plant covers. In the driest period, the shrub maintained 120% much water and the rosette a half extra than bs. Below the shrub and bs the drainage had high likely. The runoff was not detected in any cover condition. The EVT was reduced a half by plants in the dry season, being the shrub effect more markable.